2-3n=-2(n-2)

Simple and best practice solution for 2-3n=-2(n-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-3n=-2(n-2) equation:



2-3n=-2(n-2)
We move all terms to the left:
2-3n-(-2(n-2))=0
We calculate terms in parentheses: -(-2(n-2)), so:
-2(n-2)
We multiply parentheses
-2n+4
Back to the equation:
-(-2n+4)
We get rid of parentheses
-3n+2n-4+2=0
We add all the numbers together, and all the variables
-1n-2=0
We move all terms containing n to the left, all other terms to the right
-n=2
n=2/-1
n=-2

See similar equations:

| 4(k-8)=32-4k | | -8n-4(1+5n)=-6n-14 | | 18-3.x=-53 | | 2(x-2)-3(x+4)=-20 | | 18-3.x=5 | | 2/11=x/66 | | 3n-3=5n-11 | | -3(y+4)=4y-37 | | 5z-18-3z+4=60 | | 18-3.x=0 | | 4/5x=12/40 | | 18-3.x=-39 | | 2.5+12.5y=10560 | | 40/26=a+10/13 | | 2(x-4)-3(x+4)=13 | | 4(n+1)=20 | | 3/5(2x+5)=2/5(2x+7) | | 2/9n-31=16+7/9n | | 5n+3=-7 | | -12+3b=-4(3-3b) | | 1/5x=61.50 | | (F-2)-(4-f)=8 | | 6/4=2/12y | | -2(y-2)=-3-2y | | 40x+8(1.5x)=884 | | 3x/2+2x/5+5x/3=4 | | -6x-15x+7=-17 | | 5(2x+1)=5x+3x+9 | | 20/14=n+9/7 | | 2x13=75 | | -2(3x+3)=4(2x+2) | | 64x^2-6=19 |

Equations solver categories